Zirconium-containing nanoscale microporous high-temperature-resistant super thermal insulation material
Through the nano-scale microporous high-temperature super heat insulation material with a double-layer structure, the materials with different density and thermal conductivity are combined to solve the problems of high thermal conductivity and large volume density in the prior art, and realize the high temperature and low temperature Highly efficient thermal insulation and lightweight design.
Patent Information
- Application Number
- CN202411424021.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
The thermal conductivity and thermal insulation speed of existing nano-scale microporous insulation materials cannot be unified at high and low temperatures, resulting in a high thermal conductivity and large bulk density, which cannot be applied to some occasions, making it impossible to achieve more efficient, lightweight and resistant High temperature insulation material.
Nano-scale microporous high-temperature super heat insulation material adopts a bilayer structure. The surface structure consists of reinforced aluminum silicate fibers, nano-scale silica powder, nano-scale zircon sand powder, reverse infrared radiation powder and inorganic binder The inner layer structure consists of zirconium aluminum silicate fiber, nano-scale silica powder, nano-scale zircon sand powder and reverse infrared radiation powder. It is composited by materials of different density and thermal conductivity and is suitable for different temperature ranges.
It realizes the surface structure with extremely low thermal conductivity in the high temperature zone, low density and light mass, and the inner structure with large thermal conductivity and high density in the low temperature zone, overcomes the shortcomings of single-layer materials, reduces the bulk density, and is suitable for Lightweight occasions, and improve thermal insulation and high temperature resistance.
Smart Images

Figure CN119305264A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature thermal insulation materials, in particular to a zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material. Background Art
[0002] The existing nano-scale microporous thermal insulation material structure uses a single layer of nano-scale thermal insulation material, the main materials of which are nano-scale silicon dioxide and industrial ultrafine silica fume. The thermal conductivity and thermal insulation speed of the single-layer nano-scale microporous thermal insulation material for the high temperature side and the low temperature side cannot be unified, resulting in a high thermal conductivity (0.055-0.085W / mk at 371°C, see patent: CN110105044B). Moreover, the single-layer nano-scale microporous thermal insulation material is limited by its large volume density (350-800Kg / , see patent: CN109369143B), and cannot be used in some occasions. These problems are a challenge to the pursuit of more efficient, lightweight, and high temperature resistant nano-scale microporous thermal insulation materials.
[0003] There are also nano-scale microporous thermal insulation materials with multiple layers on the market, but they are composed of a thermal insulation layer, a reflective layer and a fire-resistant layer, and their thermal conductivity is also high (0.048-0.052 W / mk at 300°C). In this case, those skilled in the art need to make corresponding improvements to the structure of the single-layer nano-scale thermal insulation material. Summary of the invention
[0004] The purpose of the present invention is to provide a zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material, comprising a surface structure and an inner layer structure;
[0006] The surface structure components include: 45-55% of reinforcing zirconium-containing aluminum silicate fiber; 15-25% of nano-scale silicon dioxide powder, 10-20% of nano-scale zircon sand powder; 15-25% of anti-infrared radiation powder; 0.1-0.5% of nano-high temperature expanded graphite, and 2-5% of inorganic binder;
[0007] The inner layer structural components include: 50-75% of zirconium-containing aluminum silicate fiber; 10-20% of nanometer silicon dioxide powder, 5-10% of nanometer zircon sand powder; 10-20% of anti-infrared radiation powder and 2-5% of inorganic binder.
[0008] The zirconium content of the reinforcing zirconium-containing aluminum silicate fiber is 15-17%, and the zirconium content of the zirconium-containing aluminum silicate fiber is 3-5%.
[0009] Preferably, the surface structure is close to the high temperature side, suitable for temperature conditions of 649-1260°C, and the inner structure is close to the low temperature side, suitable for temperature conditions of 371-649°C.
[0010] Preferably, the specific surface area of the reinforced zirconium-containing aluminum silicate fiber and the zirconium-containing aluminum silicate fiber is 80-200 m2 / g, and the average particle size is 100-300 nanometers.
[0011] Preferably, the nano-scale silicon dioxide powder is fumed silicon dioxide, with a specific surface area of 180 to 400 m2 / g and a primary particle size of 7 to 10 nanometers.
[0012] Preferably, the specific surface area of the nano-scale zircon sand powder is 180 to 200 m2 / g, and the average particle size is 50 to 100 nanometers.
[0013] Preferably, the particle size of the nano-scale anti-infrared radiation powder is between 300-400 nanometers and the density is between 100-400 kg / m 3 .
[0014] Preferably, the particle size of the nano high temperature expanded graphite is 0.1 mm and the specific surface area is 0.1-1 m2 / g.
[0015] Preferably, the modulus M of the inorganic binder is 2.00±0.10 and the density is 1.35-1.5g / cm 3 .
[0016] Compared with the prior art, the invention has the following beneficial effects: the invention is composed of two materials of different temperature layers, with the material with high density and low thermal conductivity placed on the surface layer, and the material with low density and high thermal conductivity placed on the inner layer. The double-layer material suitable for different temperature ranges is used to overcome the shortcomings of the single-layer nano-scale microporous thermal insulation material structure, and the performance and high temperature resistance of the thermal insulation material are improved by using materials with different densities and different thermal conductivity coefficients.
[0017] The double-layer composite material structure of the present invention is simpler than the multi-layer nano-scale microporous thermal insulation material structure. The multi-layer nano-scale microporous thermal insulation material is composed of a thermal insulation layer, a reflective layer and a fire-resistant layer, which requires more complicated processes and structural layers. The present invention overcomes this shortcoming and is composed of different nano-scale microporous thermal insulation materials, which has the advantages of short preparation time and simple implementation.
[0018] The volume density of the product produced by the invention is lower than that of a single-layer nanometer-level microporous heat-insulating material, and the volume density is 300-500 kg / , which is suitable for lightweight occasions.
[0019] The material performance of the present invention is that the surface structure of material 1 has extremely low thermal conductivity, low density, light weight and good heat resistance near the high temperature of 1260°C; while the thermal conductivity is relatively high, the density is relatively high and the weight is large near the low temperature of 371°C. The inner layer structure has low thermal conductivity, low density, light weight and good heat resistance near 371°C; while the thermal conductivity is relatively high, the density is relatively high and the weight is heavy near 1260°C. Therefore, by using this structure of high temperature zone material and low temperature zone material, a super heat-resistant and fireproof structure with extremely low thermal conductivity, low density, light weight and good heat resistance in the full temperature zone is formed, which reduces weight and saves costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the overall structure of the present invention;
[0021] Figure 2 Schematic diagram of the proportion of surface structure materials of the present invention;
[0022] Figure 3 Schematic diagram of the proportion of inner layer structural materials of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1:
[0025] The surface nano-scale microporous thermal insulation material 1 has the following composition and weight percentages:
[0026] Reinforced zirconium-containing aluminum silicate fibers (3-5 microns in diameter and 5-8 mm in length) 55%.
[0027] Nano-scale silicon dioxide powder (fumed silicon dioxide, with a specific surface area of 300m2 / g and a primary particle size of 7 to 10 nanometers) 14.8%.
[0028] Nano-grade zircon sand powder (specific surface area of 200m2 / g, average particle size of 50-100 nanometers) 8%.
[0029] Anti-infrared radiation powder (density 150kg / m3, powder particle size 300-400 nanometers) 20%; nano high temperature expanded graphite (particle size 0.1mm, specific surface area 0.1-1m2 / g) 0.2%
[0030] Inorganic binder, liquid sodium silicate 2%
[0031] The composition and weight percentage of the inner layer nano-scale microporous thermal insulation material 2 are as follows:
[0032] Contains 75% zirconium aluminum silicate fibers (diameter 3-5 microns, length 5-8 mm).
[0033] Nano-scale silicon dioxide powder (fumed silicon dioxide, with a specific surface area of 300m2 / g and a primary particle size of 7 to 10 nanometers) 8%.
[0034] Nano-grade zircon sand powder (specific surface area of 200m2 / g, average particle size of 50-100 nanometers) 5%.
[0035] Anti-infrared radiation powder (density is 150kg / m3, and the powder particle size is 3 to 20 mm) 10%.
[0036] Inorganic binder, liquid sodium silicate 2%.
[0037] The preparation methods of both materials are the same.
[0038] The preparation method is:
[0039] According to the weight ratio, the reinforced aluminum silicate fiber containing zirconium, nano-scale silicon dioxide powder, nano-scale zircon sand powder, anti-infrared radiation powder, and nano-high-temperature expanded graphite are added with a certain amount of inorganic adhesive, water, and coagulant, and stirred, deslagging, extruded, dehydrated, solidified, and precisely pressed to obtain two nano-scale microporous high-temperature super insulation materials. The surface nano-scale microporous high-temperature super insulation material has an allowable use temperature of ≤1260℃ and a volume density of 350Kg / m 3 , the permanent linear shrinkage after heating at 1260℃ for 24 hours is ≤2.5%, the compressive strength is ≥0.3Mpa, and the thermal conductivity is 0.026~0.030W / mK at 900℃.
[0040] The inner layer nano-scale microporous high temperature resistant super thermal insulation material has an allowable use temperature of 371-649°C and a volume density of 300Kg / m 3 , the permanent linear shrinkage after heating at 371℃ for 24 hours is ≤2.5%, the compressive strength is ≥0.3Mpa, and the thermal conductivity is 0.025~0.028W / mK at 371℃.
[0041] Then, the two nano-scale microporous high-temperature resistant super insulation materials are impregnated with inorganic binders for 15-30 minutes in the order of the structure, and then placed in a firing kiln for calcination after drying. The firing temperature is 900-1000°C and the firing cycle is 10-12 hours, making the double-layer structure more stable. The new nano-scale microporous high-temperature resistant super insulation material allows the use temperature to be 1260 degrees.
[0042] Embodiment 2:
[0043] The surface nano-scale microporous thermal insulation material 1 has the following composition and weight percentages:
[0044] Reinforced with 50% zirconium-containing aluminum silicate fiber (diameter 3-5 microns, length 5-8 mm).
[0045] Nano-scale silicon dioxide powder (fumed silicon dioxide, specific surface area of 300m2 / g, primary particle size of 7-10 nanometers) 18.8%
[0046] Nano-grade zircon sand powder (specific surface area of 200m2 / g, average particle size of 50-100 nanometers) 11%.
[0047] Anti-infrared radiation powder (density 150kg / m3, powder particle size 300-400 nanometers) 18%; nano high temperature expanded graphite (particle size 0.1mm, specific surface area 0.1-1m2 / g) 0.2%
[0048] Inorganic binder, liquid sodium silicate 2%
[0049] The composition and weight percentage of the inner layer nano-scale microporous thermal insulation material 2 are as follows:
[0050] Contains 63% zirconium-aluminum silicate fibers (diameter 3-5 microns, length 5-8 mm).
[0051] Nano-scale silicon dioxide powder (fumed silicon dioxide, specific surface area of 300m2 / g, primary particle size of 7-10 nanometers) 13%
[0052] Nano-grade zircon sand powder (specific surface area of 200m2 / g, average particle size of 50-100 nanometers) 7%.
[0053] Anti-infrared radiation powder (density 150kg / m3, powder particle size 300-400 nanometers) 15%
[0054] Inorganic binder, liquid sodium silicate 2%
[0055] The preparation methods of both materials are the same.
[0056] The preparation method is:
[0057] According to the weight ratio, a certain amount of inorganic adhesive, water, and coagulant are added to the reinforced zirconium-containing aluminum silicate fiber, nano-scale silica powder, nano-scale zircon sand powder, anti-infrared radiation powder, and nano-high-temperature expanded graphite, and then stirred, deslagging, extruded, dehydrated, solidified, and precisely pressed to obtain two nano-scale microporous high-temperature resistant super thermal insulation materials. The surface nano-scale microporous high-temperature resistant super thermal insulation material has an allowable use temperature of ≤1260℃ and a volume density of 400Kg / m 3, the permanent linear shrinkage after heating at 1260℃ for 24 hours is ≤2.1%, the compressive strength is ≥0.5Mpa, and the thermal conductivity is 0.022~0.026W / mK at 900℃.
[0058] The inner layer nano-scale microporous high temperature resistant super insulation material has an allowable use temperature of 371-649°C and a volume density of 360Kg / m 3 , the permanent linear shrinkage after heating at 371℃ for 24 hours is ≤2.5%, the compressive strength is ≥0.3Mpa, and the thermal conductivity is 0.024~0.028W / mK at 371℃.
[0059] Then, the two nano-scale microporous high-temperature resistant super insulation materials are impregnated with inorganic binders for 15-30 minutes in the order of the structure, and then placed in a firing kiln for calcination after drying. The firing temperature is 900-1000°C and the firing cycle is 10-12 hours, making the double-layer structure more stable. The new nano-scale microporous high-temperature resistant super insulation material allows the use temperature to be 1260 degrees.
[0060] Embodiment 3:
[0061] The surface nano-scale microporous thermal insulation material 1 has the following composition and weight percentages:
[0062] Reinforced zirconium-containing aluminum silicate fibers (3-5 microns in diameter and 5-8 mm in length) 45%.
[0063] Nano-scale silicon dioxide powder (fumed silicon dioxide, specific surface area of 300m2 / g, primary particle size of 7-10 nanometers) 21.8%
[0064] Nano-grade zircon sand powder (specific surface area of 200m2 / g, average particle size of 50-100 nanometers) 16%.
[0065] Anti-infrared radiation powder (density 150kg / m3, powder particle size 300-400 nanometers) 15%;
[0066] Nano high temperature expanded graphite (particle size 0.1mm, specific surface area 0.1-1m2 / g) 0.2%;
[0067] Inorganic binder, liquid sodium silicate 2%;
[0068] The composition and weight percentage of the inner layer nano-scale microporous thermal insulation material 2 are as follows:
[0069] Zirconium-aluminum silicate fibers (diameter 3-5 microns, length 5-8 mm) 53%.
[0070] Nano-scale silicon dioxide powder (fumed silicon dioxide, with a specific surface area of 300m2 / g and a primary particle size of 7 to 10 nanometers) 16%;
[0071] Nano-grade zircon sand powder (specific surface area of 200m2 / g, average particle size of 50-100 nanometers) 9%.
[0072] Anti-infrared radiation powder (density 150kg / m3, powder particle size 300-400 nanometers) 10%;
[0073] Inorganic binder, liquid sodium silicate 2%;
[0074] The preparation methods of both materials are the same.
[0075] The preparation method is:
[0076] According to the weight ratio, the reinforced aluminum silicate fiber containing zirconium, nano-scale silicon dioxide powder, nano-scale zircon sand powder, anti-infrared radiation powder, and nano-high-temperature expanded graphite are added with a certain amount of inorganic adhesive, water, and coagulant, and stirred, deslagging, extruded, dehydrated, solidified, and precisely pressed to obtain two nano-scale microporous high-temperature super insulation materials. The surface nano-scale microporous high-temperature super insulation material has an allowable use temperature of ≤1260℃ and a volume density of 500Kg / m 3 , the permanent linear shrinkage after heating at 1260℃ for 24 hours is ≤1.4%, the compressive strength is ≥0.8Mpa, and the thermal conductivity is 0.020~0.023W / mK at 900℃.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material, characterized in that: Including surface structure and inner structure; The surface structure components include: 45-55% of reinforcing zirconium-containing aluminum silicate fiber; 15-25% of nano-scale silicon dioxide powder, 10-20% of nano-scale zircon sand powder; 15-25% of anti-infrared radiation powder; 0.1-0.5% of nano-high temperature expanded graphite, and 2-5% of inorganic binder; The inner layer structural components include: 50-75% of zirconium-containing aluminum silicate fiber; 10-20% of nanometer silicon dioxide powder, 5-10% of nanometer zircon sand powder; 10-20% of anti-infrared radiation powder and 2-5% of inorganic binder.
2. The zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material according to claim 1, characterized in that: The surface structure is close to the high temperature side and is suitable for temperature conditions of 649-1260℃, while the inner structure is close to the low temperature side and is suitable for temperature conditions of 371-649℃.
3. The zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material according to claim 2, characterized in that: The specific surface area of the reinforced zirconium-containing aluminum silicate fiber and the zirconium-containing aluminum silicate fiber is 80-200m2 / g, and the average particle size is 100-300 nanometers.
4. The zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material according to claim 3, characterized in that: Nano-scale silicon dioxide powder is fumed silicon dioxide with a specific surface area of 180 to 400 m2 / g and a primary particle size of 7 to 10 nanometers.
5. The zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material according to claim 4, characterized in that: The specific surface area of nano-scale zircon sand powder is 180-200m2 / g, and the average particle size is 50-100 nanometers.
6. The zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material according to claim 1, characterized in that: The particle size of nano-scale anti-infrared radiation powder is between 300-400 nanometers, and the density is between 100-400 kg / m 3 .
7. The zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material according to claim 1, characterized in that: The particle size of nano high temperature expanded graphite is 0.1mm and the specific surface area is 0.1-1m2 / g.
8. The zirconium-containing nano-scale microporous high-temperature resistant super thermal insulation material according to claim 1, characterized in that: The modulus M of the inorganic binder is 2.00±0.10, and the density is 1.35-1.5g / cm 3 .
Citation Information
Patent Citations
A high-strength nano-micro-porous thermal insulation material
CN109369143B
A lightweight, high-strength nanoscale microporous thermal insulation material
CN110105044B
Ceramic fiber plate and preparation method thereof
CN104446222A
High-strength nano-micron microporous insulation material
CN109369143A
Gradient nano thermal insulation material and preparation method thereof
CN110511048A